2018
DOI: 10.1371/journal.pone.0207784
|View full text |Cite
|
Sign up to set email alerts
|

Automated algorithms combining structure and function outperform general ophthalmologists in diagnosing glaucoma

Abstract: PurposeTo test the ability of machine learning classifiers (MLCs) using optical coherence tomography (OCT) and standard automated perimetry (SAP) parameters to discriminate between healthy and glaucomatous individuals, and to compare it to the diagnostic ability of the combined structure-function index (CSFI), general ophthalmologists and glaucoma specialists.DesignCross-sectional prospective study.MethodsFifty eight eyes of 58 patients with early to moderate glaucoma (median value of the mean deviation = −3.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 44 publications
(54 reference statements)
2
17
0
2
Order By: Relevance
“…In addition, the diagnostic accuracy of general ophthalmologists (0.8195) was lower than MLCs. Interestingly, studies comparing diagnosing ability between AI and ophthalmologists often shows better performance of AI, which are similar to our results [37,47]. Therefore, we can predict that in the future application of machine diagnosis, it can help general ophthalmologists and primary hospitals to make more accurate prediction and avoid missed diagnosis or misdiagnosis to some extent.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the diagnostic accuracy of general ophthalmologists (0.8195) was lower than MLCs. Interestingly, studies comparing diagnosing ability between AI and ophthalmologists often shows better performance of AI, which are similar to our results [37,47]. Therefore, we can predict that in the future application of machine diagnosis, it can help general ophthalmologists and primary hospitals to make more accurate prediction and avoid missed diagnosis or misdiagnosis to some extent.…”
Section: Discussionsupporting
confidence: 88%
“…Previous attempts have been made to combine structure and function to detect POAG. In the studies of Raza et al[36] and Leonardo et al [37], researchers combined OCT and SAP results, and the results obtained were better than that obtained by analyzing OCT results alone, indicating that structure and function combining models show better diagnostic results. Kim et al…”
Section: Discussionmentioning
confidence: 99%
“…Further, clinicians are encouraged to confirm a suspected structural lesion in the functional domain to increase confidence in diagnosis. [16][17][18][19] Enface images offer the opportunity to relate structure and function without use of structure-function maps, thought to represent an additional source of noise in this relationship. 20 Indeed, newer perimetric strategies that aim to incorporate structural information for greater efficiency, [21][22][23] or that assess specific regions of interest in greater detail, [24][25][26] may be facilitated by enface imaging.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that disruption of RNFB reflectivity may be measurable earlier than RNFL thinning in glaucoma, 8,15 making this approach encouraging for earlier identification of defects. Further, clinicians are encouraged to confirm a suspected structural lesion in the functional domain to increase confidence in diagnosis 16–19 . Enface images offer the opportunity to relate structure and function without use of structure‐function maps, thought to represent an additional source of noise in this relationship 20 .…”
Section: Introductionmentioning
confidence: 99%
“…As an example, previous studies have used SVMs to improve detection of glaucoma damage from imaging data. [11][12][13] The SVMs used features such as global and sectoral parameters of retinal nerve fiber layer (RNFL) thickness, and measurements such as rim and cup area, cleverly combining them to reach a final glaucoma classification. However, although satisfactory performance has been reported for SVMs and other traditional algorithms in this scenario, there is no guarantee that the parameters used as initial features make the best use of the vast information produced by imaging.…”
Section: Artificial Intelligence Machine Learning and Deep Learningmentioning
confidence: 99%